High power 2.5D integrated thermoelectric generators combined with microchannels technology. (1st August 2022) - Savelli, Guillaume; Colonna, Jean-Philippe; Coudrain, Perceval; Faucherand, Pascal; Royer, Agnès; Collin, Louis-Michel; Amnache, Amrid; Fréchette, Luc
Abstract: We have developed high power integrated thermoelectric generators (μTEGs). These μTEGs are CMOS compatible, i.e. based on polycristalline SiGe materials. These μTEGs have been processed directly on a silicon interposer. Even if poly-SiGe exhibits low thermoelectric performances at room temperature, the specific design and proposed architecture enable μTEGs to deliver up to 680 μW for a temperature difference at 15.5 K. To reach such high power, an original 2.5D structure has been developed and μchannels technology has been associated, below the μTEG, to dissipate heat coming from the hot side. μTEGs have been tested in real environment, located below a hot test chip. Such μTEG performances overtake those from similar state-of-the-art CMOS compatible devices, and pave the way for a potential use in different applications such as sensors power supply or battery charger. Highlights: A CMOS compatible μthermoelectric generator (μTEG) has been developed using a specific 2.5D architecture. μTEG has also be associated to μchannel technology to dissipate the heat. μTEG has been tested in real case using a thermal test chip. Electrical properties of μTEG have been measured highlighting the influence of the 2.5D architecture. μTEG performances measured overtake those from similar state-of-the-art CMOS compatible devices.